Hadith #1753 - Sahih al-Bukhari - Abdullah bin (Sahih al-Bukhari)
My father set out (for Mecca) in the year of Al-Hudaibiya, and his companions assumed Ihram, but he did not. At that time the Prophet (ﷺ) was informed that an enemy wanted to attack him, so the Prophet (ﷺ) proceeded onwards. While my father was among his companions, some of them laughed among themselves. (My father said), “I looked up and saw an onager. I attacked, stabbed and caught it. I then sought my companions’ help but they refused to help me. (Later) we all ate its meat. We were a
Grade: Sahih

Hadith #1754 - Sahih al-Bukhari - Abdullah bin (Sahih al-Bukhari)
That his father said “We proceeded with the Prophet (ﷺ) in the year of Al-Hudaibiya and his companions assumed Ihram but I did not. We were informed that some enemies were at Ghaiqa and so we went on towards them. My companions saw an onager and some of them started laughing among themselves. I looked and saw it. I chased it with my horse and stabbed and caught it. I wanted some help from my companions but they refused. (I slaughtered it all alone). We all ate from it (i.e. its meat). Then I
Grade: Sahih

Hadith #1755 - Sahih al-Bukhari - Abu Qatada ibn Rab'i (Sahih al-Bukhari)
We were in the company of the Prophet (ﷺ) at a place called Al-Qaha (which is at a distance of three stages of journey from Medina). Abu Qatada narrated through another group of narrators: We were in the company of the Prophet (ﷺ) at a place called Al-Qaha and some of us had assumed Ihram while the others had not. I noticed that some of my companions were watching something, so I looked up and saw an onager. (I rode my horse and took the spear and whip) but my whip fell down (and I asked the
Grade: Sahih

Hadith #1756 - Sahih al-Bukhari - Abdullah bin (Sahih al-Bukhari)
That his father had told him that Allah’s Messenger (ﷺ) set out for Hajj and so did his companions. He sent a batch of his companions by another route and Abu Qatada was one of them. The Prophet (ﷺ) said to them, “Proceed along the seashore till we meet all together.” So, they took the route of the seashore, and when they started all of them assumed Ihram except Abu Qatada. While they were proceeding on, his companions saw a group of onagers. Abu Qatada chased the onagers and attacked
Grade: Sahih

Hadith #1757 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
From As-Sa’b bin Jath-thama Al-Laithi that the latter presented an onager to Allah’s Messenger (ﷺ) while he was at Al-Abwa’ or at Waddan, and he refused it. On noticing the signs of some unpleasant feeling of disappointment on his (As-Sab’s) face, the Prophet (ﷺ) said to him, “I have only returned it because I am Muhrim.”
Grade: Sahih

Hadith #1758 - Sahih al-Bukhari - ibn Umar (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) said, “It is not sinful of a Muhrim to kill five kinds of animals.”
Grade: Sahih

Hadith #1759 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ﷺ) said, “A Muhrim can kill (five kinds of animals.)”
Grade: Sahih

Hadith #1760 - Sahih al-Bukhari - Hafsa bint 'Abdur-Rahman ibn Abi Bakr حفصة بنت عبد الرحمن بن أبي بكر الصديق (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) said, “It is not sinful (of a Muhrim) to kill five kinds of animals, namely: the crow, the kite, the mouse, the scorpion and the rabid dog.”
Grade: Sahih

Hadith #1761 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) said, “Five kinds of animals are harmful and could be killed in the Haram (Sanctuary). These are: the crow, the kite, the scorpion, the mouse and the rabid dog.”
Grade: Sahih

Hadith #1762 - Sahih al-Bukhari - Abdullah bin (Sahih al-Bukhari)
While we were in the company of the Prophet (ﷺ) in a cave at Mina, when Surat-wal-Mursalat were revealed and he recited it and I heard it (directly) from his mouth as soon as he recited its revelation. Suddenly a snake sprang at us and the Prophet (ﷺ) said (ordered us): “Kill it.” We ran to kill it but it escaped quickly. The Prophet (ﷺ) said, “It has escaped your evil and you too have escaped its evil.”
Grade: Sahih

Hadith #1763 - Sahih al-Bukhari (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) called the salamander a bad animal, but I did not hear him ordering it to be killed.”
Grade: Sahih

Hadith #1764 - Sahih al-Bukhari - S'aid bin Qays bin Qahd سعيد بن قيس بن قهد الأنصاري (Sahih al-Bukhari)
Abu Shuraih, Al-`Adawi said that he had said to `Amr bin Sa`id when he was sending the troops to Mecca (to fight `Abdullah bin Az-Zubair), “O Chief! Allow me to tell you what Allah’s Messenger (ﷺ) said on the day following the Conquest of Mecca. My ears heard that and my heart understood it thoroughly and I saw with my own eyes the Prophet (ﷺ) when he, after Glorifying and Praising Allah, started saying, ‘Allah, not the people, made Mecca a sanctuary, so anybody who has belief in Allah
Grade: Sahih

Hadith #1765 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
“The Prophet (ﷺ) said, ‘Allah has made Mecca, a sanctuary, so it was a sanctuary before me and will continue to be a sanctuary after me. It was made legal for me (i.e. I was allowed to fight in it) for a few hours of a day. It is not allowed to uproot its shrubs or to cut its trees, or to chase (or disturb) its game, or to pick up its luqata (fallen things) except by a person who would announce that (what he has found) publicly.’ Al-`Abbas said, ‘O Allah’s Messenger (ﷺ)! Except Al-
Grade: Sahih

Hadith #1766 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
On the day of the conquest of Mecca, the Prophet (ﷺ) said, “There is no more emigration (from Mecca) but Jihad and intentions, and whenever you are called for Jihad, you should go immediately. No doubt, Allah has made this place (Mecca) a sanctuary since the creation of the heavens and the earth and will remain a sanctuary till the Day of Resurrection as Allah has ordained its sanctity. Fighting was not permissible in it for anyone before me, and even for me it was allowed only for a portion
Grade: Sahih

Hadith #1767 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) was cupped while he was in a state of Ihram.
Grade: Sahih

Hadith #1768 - Sahih al-Bukhari - Ibn Buhaina (Sahih al-Bukhari)
The Prophet, while in the state of Ihram, was cupped at the middle of his head at Liha-Jamal.
Grade: Sahih

Hadith #1769 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
The Prophet (ﷺ) married Maimuna while he was in the state of Ihram, (only the ceremonies of marriage were held).
Grade: Sahih

Hadith #1770 - Sahih al-Bukhari - ibn Umar (Sahih al-Bukhari)
A person stood up and asked, “O Allah’s: Apostle! What clothes may be worn in the state of Ihram?” The Prophet (ﷺ) replied, “Do not wear a shirt or trousers, or any headgear (e.g. a turban), or a hooded cloak; but if somebody has no shoes he can wear leather stockings provided they are cut short off the ankles, and also, do not wear anything perfumed with Wars or saffron, and the Muhrima (a woman in the state of Ihram) should not cover her face, or wear gloves.”
Grade: Sahih

Hadith #1771 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
A man was crushed to death by his she-camel and was brought to Allah’s Messenger (ﷺ) who said, “Give him a bath and shroud him, but do not cover his head, and do not bring any perfume near to him, as he will be resurrected reciting Talbiya.”
Grade: Sahih

Hadith #1772 - Sahih al-Bukhari - Abdullah bin (Sahih al-Bukhari)
`Abdullah bin Al-Abbas and Al-Miswar bin Makhrama differed at Al-Abwa’; Ibn `Abbas said that a Muhrim could wash his head; while Al-Miswar maintained that he should not do so. `Abdullah bin `Abbas sent me to Abu Aiyub Al-Ansari and I found him bathing between the two wooden posts (of the well) and was screened with a sheet of cloth. I greeted him and he asked who I was. I replied, “I am `Abdullah bin Hunain and I have been sent to you by Ibn `Abbas to ask you how Allah’s Messenger (ﷺ) us
Grade: Sahih

Hadith #1773 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
I heard the Prophet (ﷺ) delivering a sermon at `Arafat saying, “If a Muhrim does not find slippers, he could wear Khuffs (socks made from thick fabric or leather, but he has to cut short the Khuffs below the ankles), and if he does not find an Izar (a waist sheet for wrapping the lower half of the body) he could wear trousers.”
Grade: Sahih

Hadith #1774 - Sahih al-Bukhari - Abdullah bin (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) was asked what sort of clothes a Muhrim should wear. He replied, “He should not wear a shirt, turbans, trousers, a hooded cloak, or a dress perfumed with saffron or Wars; and if slippers are not available he can wear Khuffs (socks made from thick fabric or leather) but he should cut them so that they reach below the ankles.
Grade: Sahih

Hadith #1775 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
The Prophet (ﷺ) delivered a sermon at `Arafat and said, “Whoever does not get an Izar can wear trousers, and whoever cannot get a pair of shoes can wear Khuffs (socks made from thick fabric or leather).”
Grade: Sahih

Hadith #1776 - Sahih al-Bukhari - Al Bara (Sahih al-Bukhari)
The Prophet (ﷺ) assumed Ihram for Umra in the month of Dhul-Qa’da but the (pagan) people of Mecca refused to admit him into Mecca till he agreed on the condition that he would not bring into Mecca any arms but sheathed.
Grade: Sahih

Hadith #1777 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
The Prophet (ﷺ) fixed Dhul-Hulaifa as the Miqat (the place for assuming Ihram) for the people of Medina, and Qaran-al-Manazil for the people of Najd, and Yalamlam for the people of Yemen. These Mawaqit are for those people and also for those who come through these Mawaqit (from places other than the above-mentioned) with the intention of (performing) Hajj and Umra. And those living inside these Mawaqit can assume Ihram from the place where they start; even the people of Mecca can assume Ihram
Grade: Sahih

Hadith #1778 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) entered Mecca in the year of its Conquest wearing an Arabian helmet on his head and when the Prophet (ﷺ) took it off, a person came and said, “Ibn Khatal is holding the covering of the Ka`ba (taking refuge in the Ka`ba).” The Prophet (ﷺ) said, “Kill him.”
Grade: Sahih

Hadith #1779 - Sahih al-Bukhari - Ali (Sahih al-Bukhari)
While I was with Allah’s Messenger (ﷺ) there came to him a man wearing a cloak having a trace of yellowish perfume or a similar thing on it. `Umar used to say to me, “Would you like to see the Prophet (ﷺ) at the time when he is inspired divinely?” So, it happened that he was inspired (then) and when the inspiration was over the Prophet (ﷺ) said (to that man), “Do in your `Umra the same as you do in your Hajj.”
Grade: Sahih

Hadith #1780 - Sahih al-Bukhari (Sahih al-Bukhari)
A man bit the hand of another man but in that process the latter broke one incisor tooth of the former, and the Prophet (ﷺ) forgave the latter.
Grade: Sahih

Hadith #1781 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
While a man was standing with the Prophet (ﷺ) at `Arafat, he fell from his Mount and his neck was crushed by it. The Prophet (ﷺ) said, “Wash the deceased with water and Sidr and shroud him in two pieces of cloth, and neither perfume him nor cover his head, for Allah will resurrect him on the Day of Resurrection and he will be reciting Talbiya.”
Grade: Sahih

Hadith #1782 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
While a man was standing with the Prophet (ﷺ) at `Arafat, he fell from his Mount and his neck was crushed by it. The Prophet (ﷺ) said, “Wash the deceased with water and Sidr and shroud him in two pieces of cloth, and neither perfume him nor cover his head, for Allah will resurrect him on the Day of Resurrection and he will be reciting Talbiya.”
Grade: Sahih

Hadith #1783 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
A man was in the company of the Prophet (ﷺ) and his she-camel crushed his neck while he was in a state of Ihram and he died Allah’s Messenger (ﷺ) said, “Wash him with water and Sidr and shroud him in his two garments; neither perfume him nor cover his head, for he will be resurrected on the Day of Resurrection, reciting Talbiya.”
Grade: Sahih

Hadith #1784 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
A woman from the tribe of Juhaina came to the Prophet (ﷺ) and said, “My mother had vowed to perform Hajj but she died before performing it. May I perform Hajj on my mother’s behalf?” The Prophet (ﷺ) replied, “Perform Hajj on her behalf. Had there been a debt on your mother, would you have paid it or not? So, pay Allah’s debt as He has more right to be paid.”
Grade: Sahih

Hadith #1785 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
A woman from the tribe of Khath’am came in the year (of ,Hajjat-al-Wada` of the Prophet (ﷺ) ) and said, “O Allah’s Messenger (ﷺ)! My father has come under Allah’s obligation of performing Hajj but he is a very old man and cannot sit properly on his Mount. Will the obligation be fulfilled if I perform Hajj on his behalf?” The Prophet (ﷺ) replied in the affirmative.
Grade: Sahih

Hadith #1786 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
Al-Fadl was riding behind the Prophet (ﷺ) and a woman from the tribe of Khath’am came up. Al-Fadl started looking at her and she looked at him. The Prophet (ﷺ) turned Al-Fadl’s face to the other side. She said, “My father has come under Allah’s obligation of performing Hajj but he is a very old man and cannot sit properly on his Mount. Shall I perform Hajj on his behalf? The Prophet (ﷺ) replied in the affirmative. That happened during Hajjat-al-Wada` of the Prophet (ﷺ) .
Grade: Sahih

Hadith #1787 - Sahih al-Bukhari - Abdullah bin (Sahih al-Bukhari)
Al Fadl was riding behind the Prophet (ﷺ) and a woman from the tribe of Khath’am came up. Al Fadl started looking at her and she looked at him. The Prophet (ﷺ) turned Al-Fadl’s face to the other side. She said, “My father has come under Allah’s obligation of performing Hajj but he is very old man and cannot sit properly on his Rahila (mount). Shall I perform Hajj on his behalf ? The Prophet (ﷺ) replied affirmative. That happened during Hajjat-ul-Wada’ of the Prophet (ﷺ).
Grade: Sahih

Hadith #1788 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
The Prophet (ﷺ) sent me (to Mina) with the luggage from Jam’ (i.e. Al-Muzdalifa) at night.
Grade: Sahih

Hadith #1789 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
I came riding on my she-ass and had (just) then attained the age of puberty. Allah’s Messenger (ﷺ) was praying at Mina. I passed in front of a part of the first row and then dismounted from it, and the animal started grazing. I aligned with the people behind Allah’s Messenger (ﷺ) (The sub-narrator added that happened in Mina during the Prophet’s Hajjat-al-Wada`.)
Grade: Sahih

Hadith #1790 - Sahih al-Bukhari - As-Sa'ib bin Yazid (Sahih al-Bukhari)
(While in the company of my parents) I was made to perform Hajj with Allah’s Messenger (ﷺ) and I was a seven-year-old boy then. (Fath-ul-Bari, p.443, Vol.4)
Grade: Sahih

Hadith #1791 - Sahih al-Bukhari - al-J'ad bin 'Abdur Rahman الجعد/الجعيد بن عبد الرحمن بن أوس (Sahih al-Bukhari)
I heard `Umar bin `Abdul `Aziz telling about As-Sa’ib bin Yazid that he had performed Hajj (while carried) with the belongings of the Prophet.
Grade: Sahih

Hadith #1792 - Sahih al-Bukhari (Sahih al-Bukhari)
Narrated Ibrahim’s grand-father that ‘Umar(ra) in his last Hajj allowed the wives of the Prophet(ﷺ)to perform Hajj and he sent with them ‘Uthman bin ‘Affan(ra) and ‘Abdur-Rahman bin ‘Auf(ra) as escorts.
Grade: Sahih

Hadith #1793 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
I said, “O Allah’s Messenger (ﷺ)! Shouldn’t we participate in Holy battles and Jihad along with you?” He replied, “The best and the most superior Jihad (for women) is Hajj which is accepted by Allah.” `Aisha added: Ever since I heard that from Allah’s Messenger (ﷺ) I have determined not to miss Hajj.
Grade: Sahih

Hadith #1794 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
The Prophet (ﷺ) said, “A woman should not travel except with a Dhu-Mahram (her husband or a man with whom that woman cannot marry at all according to the Islamic Jurisprudence), and no man may visit her except in the presence of a Dhu-Mahram.” A man got up and said, “O Allah’s Messenger (ﷺ)! I intend to go to such and such an army and my wife wants to perform Hajj.” The Prophet (ﷺ) said (to him), “Go along with her (to Hajj).
Grade: Sahih

Hadith #1795 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
When the Prophet (ﷺ) returned after performing his Hajj, he asked Um Sinan Al-Ansari, “What did forbid you to perform Hajj?” She replied, “Father of so-and-so (i.e. her husband) had two camels and he performed Hajj on one of them, and the second is used for the irrigation of our land.” The Prophet (ﷺ) said (to her), “Perform `Umra in the month of Ramadan, (as it is equivalent to Hajj or Hajj with me (in reward).
Grade: Sahih

Hadith #1796 - Sahih al-Bukhari - Qaza'a the slave of Ziyad (Sahih al-Bukhari)
Abu Sa`id who participated in twelve Ghazawat with the Prophet (ﷺ) said, “I heard four things from Allah’s Messenger (ﷺ) (or I narrate them from the Prophet (ﷺ) ) which won my admiration and appreciation. They are: -1. “No lady should travel without her husband or without a Dhu-Mahram for a two-days’ journey. -2. No fasting is permissible on two days of `Id-ul-Fitr, and `Id-al-Adha. -3. No prayer (may be offered) after two prayers: after the `Asr prayer till the sun set and after t
Grade: Sahih

Hadith #1797 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
The Prophet (ﷺ) saw an old man walking, supported by his two sons, and asked about him. The people informed him that he had vowed to go on foot (to the Ka`ba). He said, “Allah is not in need of this old man’s torturing himself,” and ordered him to ride.
Grade: Sahih

Hadith #1798 - Sahih al-Bukhari - Uqba bin 'Amir al-Juhayni (Sahih al-Bukhari)
My sister vowed to go on foot to the Ka`ba, and she asked me to take the verdict of the Prophet (ﷺ) about it. So, I did and the Prophet (ﷺ) said, “She should walk and also should ride.” Narrated Abul-Khair from `Uqba as above.:
Grade: Sahih